A national survey of ambient air pollution health literacy among adult residents of Taiwan - Wen-Hsuan Hou; Yi-Chin Huang; Chien-Yeh Lu; I-Chen Chen; Pei-Chen Lee; Ming-Yeng Lin; Yu-Chen Wang; Lilis Sulistyorini; Chung-Yi Li (BMC, 2021)
Abstract Objective To investigate the level of and covariates associated with ambient air pollution health literacy (AAPHL) among adult residents of Taiwan. Methods With a cross-sectional study design, we conducted telephone interviews using a Chinese version AAPHL scale, which consisted of 24 items assessing 12 subdomains of AAPHL formed by 4 information processing competence matrices (i.e., access, understand, appraise, and apply) and 3 health contexts (i.e., healthcare, disease prevention, and health promotion). The AAPHL was with the lowest and highest score at 1 to 4, respectively. Between September and November 2020, a sample of 1017 and 280 adults was successfully interviewed via home phones and mobile phones, respectively. We employed multiple linear regression models to identify covariates significantly associated with overall and 4 matric-specific AAPHL scores. Results The mean and standard deviation (±SD) of overall AAPHL score was considered as moderate at 2.90 (±0.56), with the highest and lowest metric-specific score for "apply" (3.07 ± 0.59) and "appraise" (2.75 ± 0.66). Lower education was significantly associated with a lower overall score; and living with children < 12 years and single were both significantly associated with higher overall scores. We also noted a significant geographic variation in overall score in which people living in the east/remote islands had highest scores. Conclusions People in Taiwan had only moderate level of AAPHL; and covariates including education, living arrangement, marital status, and area of living were significantly associated with AAPHL. These covariates should be considered in future educational interventions aiming to improve the AAPHL in the community.